Eating habits, lifestyle behaviors and stress during the COVID-19 pandemic quarantine among Peruvian adults - Hellen S. Agurto; Ana L. Alcantara-Diaz; Eduardo Espinet-Coll; Carlos J. Toro-Huamanchumo (PeerJ, 2021)
Background and aims The coronavirus disease 2019 (COVID‐19) outbreak has led to an unprecedented public health crisis. In Peru, although the quarantine is no longer mandatory, it was during the first months of 2020. To date, no studies have assessed the impact of the COVID-19 on the eating patterns and lifestyle context in the country. We aimed to describe the eating habits, lifestyle behaviors and stress during the COVID-19 pandemic quarantine among Peruvian adults. Methods We conducted a cross-sectional study. We used an online survey to collect information regarding eating habits, self-perceived stress and sedentary lifestyle among adults over 18 years of age residing in Lima-Peru and who complied with strict home quarantine. We presented our data according to the weight variation of the participants. Results A total of 686 were finally included in the study. The 82.9% were female, the median BMI was 25.97 kg/m2 (IQR: 23.37–29.41) and 68.2% reported a significant variation in their weight (38.9% increased and 29.3% lost weight). All bad habits were significantly associated with weight gain, except for prolonged fasting. Additionally, a sitting time longer than usual (p = 0.001), being in front of a screen for more than five hours in the last week (p = 0.002), and most of the stressful scenarios were significantly associated with weight gain. Conclusion Almost four out of ten participants gained weight during the quarantine. This was associated with unhealthy eating habits, physical inactivity, and stressful scenarios.